2013
DOI: 10.3109/14397595.2013.854052
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood mononuclear cell microchimerism in Turkish female patients with systemic sclerosis

Abstract: Various etiological factors rather than just one play a role in the development of scleroderma. Mc is thought to be one factor that shortens the elapsed time of disease development in SSc. Mc is inversely related to the ModRSS, and no association was detected between Mc and autoantibodies or the clinical subsets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…QuestionnaireNo significant relationship was found for either birth order or family size with SSc. SSc patients were more likely to be multiparous than controls (OR = 1.8; 95% CI: 1.1, 2.98)Şahin et al 2013 Turkey [64] Case–control. 80 female SSc patients and 40 healthy female controlsMicrochimerism and parity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…QuestionnaireNo significant relationship was found for either birth order or family size with SSc. SSc patients were more likely to be multiparous than controls (OR = 1.8; 95% CI: 1.1, 2.98)Şahin et al 2013 Turkey [64] Case–control. 80 female SSc patients and 40 healthy female controlsMicrochimerism and parity.…”
Section: Resultsmentioning
confidence: 99%
“…The possible effects of microchimerism as a risk factor for SSc were investigated in eight of the articles included in this review [12, 47, 48, 53, 59, 61, 63, 64]. Five of these articles reported microchimerism as being more common in SSc patients than in controls and found a positive relationship between SSc and a history of pregnancy (especially a history of having had a son) [47, 48, 53, 59, 64]. The other three studies failed to show a relationship and argued against microchimerism as a risk factor [12, 61, 63].…”
Section: Resultsmentioning
confidence: 99%
“…In their study on the association of Mc with clinical subsets of scleroderma, Sahin et al concluded that Mc can shorten the elapsed time of disease development in scleroderma patients; however, it was determined to have no association with clinical presentations of the disease [9]. On the other hand, another investigation into the effects of number of parities and gender of children on the epidemiology and pathogenesis of scleroderma detected no sig-doi: 10.22631/rr.2019.69997.1061…”
Section: Introductionmentioning
confidence: 99%